PELATIHAN BISNIS CANVAS MODEL DAN SOSIALISASI APLIKASI CIS SMESCO UNTUK UMKM SEBAGAI UPAYA KESIAPAN GO PUBLIC DI BANGKA BELITUNG - Sumiyati Sumiyati; Muhammad Faisal Akbar (Universita Bangka Belitung, 2022)
The canvas business model training program and the socialization of the SMESCO CIS application aim to provide education for MSME actors to manage their business. The business canvas model is a business model that helps business actors in designing their business. CIS SMESCO itself is an integrated business application for Cooperatives and MSMEs in Indonesia. This program is very important as a form of support for the Government in realizing Cooperatives and MSMEs to go digital as well as go public. The method of implementing this training uses the lecture method. The participants were 50 people who were MSME actors who had just started their business. The activity is carried out online in approximately 90 minutes. Evaluation of activities was carried out by distributing feedback questionnaires using google forms a few minutes before the event took place. The results of the evaluation showed that 80% of the participants considered this activity very informative and understood the material presented by the resource persons. This activity is beneficial for MSME actors to transform digitally and in an effort to go public. This activity needs to be carried out offline by helping participants to start digitizing their business.